Analysis of the employment status of graduates of educational sciences: case study - mohammad sharafi; مینا مقدم (Allameh Tabataba'i University Press, 2016)
Aims: This study was an attempt to examine the employment status of the graduates . The authors tried to determine to what extent the graduates were employed in organizations and companies that were related to their field of study and to what extent the university prepared the graduates for the work market. In addition, The participants of the study consisted of three groups of graduates between the years 2004 and 2008. Methods: The research method used in this research is descriptive and survey-based approach. The method used for sampling was accessible method. Data was collected through a questionnaire and analysed by the descriptive methods.Results:The main results were: 1) the employment rate of graduates while studying in the master level was 22.5 percent, and after graduation this rates reached 80 percent, and 2) most of the graduates worked in the public sector especially in higher education and educational training system. Additionally, the rate of employment in the industrial sector has increased in recent years. Conclusion: The results reveal that the duration between graduation and employment ranged from 3 months to 1 year. Eventually, the suggestion of graduates for the optimal preparing of students for the work market is offered.